Structure, Kinetics, and Function of Human and Rhesus Plasma Prekallikreins Are Similar - Veloso, Dulce; Smith, Joseph I; Denny, Stephen; Cosgriff, Thomas M (Thrombosis and Haemostasis, 1992)
To determine if rhesus monkeys (Macaca mulatta) could serve as a model for studying the role of the contact system in the pathophysiology of human infections, we compared structural, kinetic, and functional characteristics of plasma prekallikrein and its activation products in rhesus and humans. Three prekallikrein variants (85-, 89- and 93-kDa) were revealed in rhesus plasma as compared with the two variants (85- and 88-kDa) in human plasma by immunoblotting with the monoclonal antibody MAb 13G11. The prekallikrein concentration in rhesus plasma was 1.5-fold that in human plasma as determined by computerized immunoblot analyses (CIBA) and amidolytic activity. The electrophoretic mobility of prekallikrein from plasma of both species increased after deglycosylation. Inhibition of prekallikrein activation by MAb 13G11 was 55% (rhesus plasma) and 76% (human plasma), with similar inhibition curves. Immunoblots of activated rhesus plasma showed prekallikrein, complexes of kallikrein with C1 inhibitor, α2-macroglobulin and ~60-kDa inhibitor(s) (viz. antithrombin III), and 45-kDa fragments, like those in activated human plasma. Concentrations and molecular masses of factor XII and high molecular weight kininogen were similar in rhesus and human plasma. The activated partial thromboplastin time (APTT) and prothrombin time were 20.1 ± 1.6 and 9.7 ± 0.3 s for rhesus and 32.0 ±5.6 and 12 ± 0.5 s for human plasma. Human and rhesus APTTs were similar when prekallikrein concentrations in human and rhesus plasma became alike by adding human purified prekallikrein. We conclude that the contact systems of rhesus and humans are similar in many respects and that rhesus should be a useful model to study the role of the contact system in the pathophysiology of human infectious diseases.